UPAYA PENINGKATAN KOMPETENSI KINERJA SUMBER DAYA MANUSIA PERSONIL POLRI DI UNIT IDENSOS SATGASWIL DIY DENSUS 88 AT POLRI - Kurniawan, Yanche Yohan; Setyawati, Rufaida (Jurnal Riset Manajemen Akuntansi Indonesia, 2024)
The purpose of this research is to describe the Efforts to Improve the Performance Competency of the Human Resources of Polri Personnel in the Idensos Unit, Satgaswil DIY Densus 88 At Polri, which are still not optimal in terms of skills, knowledge and attitude, to identify obstacles in improving the Performance Competency of the Human Resources of Polri Personnel in the Unit Idensos Satgaswil DIY Detachment 88 At Polri, to obtain efforts to improve the Competency of Human Resource Performance for Polri Personnel in the Idensos Unit of the Special Task Force for DIY Densus 88 At Polri. This research is a qualitative research with 3 Polri personnel as respondents in the Idensos Unit of the DIY Special Detachment 88 AT Polri consisting of 1 head of the Sumda division, 1 Kanidensos Special Detachment 88 AT Polri Yogyakarta Region and 1 member. While the object of research is the Competency Improvement of the Performance of Human Resources for Polri Personnel in the Idensos Unit of the DIY Special Detachment 88 At Polri, and analyzed by Miles and Huberman data analysis. As a result, the competence of Polri Personnel in the Idensos Unit, Satgaswil DIY Densus 88 At Polr in carrying out identification and socialization activities for people/groups suspected of being related to terrorist network groups, suspects of criminal acts of terrorism after arrest, defendants, convicts and former convicts of terrorism crimes and their families in the region Yogyakarta in terms of (1) the skills of Polri personnel in the Idensos Unit of the DIY Special Detachment 88 At Polri are still not optimal so they still need to be improved considering the limited personnel. (2) Knowledge of Polri Personnel in the Idensos Unit of the DIY Special Detachment 88 At Polri is still not optimal where personnel who have the ability as investigators, identification and outreach are still lacking, (3) Attitude of Polri Personnel in the Idensos Unit of the DIY Special Detachment 88 At Polri are good, honest and responsible and have an open mind, willing to accept good suggestions and feedback, but only a few personnel have religious understanding so it needs to be improved. Obstacles in increasing the competence of personnel are the limited number of Polri personnel in the Idensos Unit of the DIY Special Detachment 88 At Polri, limited personnel who have investigator qualifications, identification and socialization, as well as religious knowledge, and still limited facilities and infrastructure both in quality and quantity so that operations are not carried out can be carried out optimally. Efforts to increase the competence of the Human Resources Performance of Polri Personnel in the Idensos Unit of the DIY Special Detachment Unit 88 At Polri which can be (1) improve coordination with Special Detachment 88 AT Yogyakarta Region, (2) increase the competence of personnel in the fields of investigators, identification, socialization and religious knowledge and (3) Efforts are made by improving facilities and infrastructure as well as increasing guidance.